Effects of physical activity on executive function and its subdomains in children aged 5–6 - Wang, Baolong; Chen, Peiyou; Jia, Zhihao; Tan, Zhaowen (Frontiers in Psychology, 2025)
ObjectiveThe purpose of this study is to explore the effect of physical activity on the executive function of 5–6-year-old children and to provide a theoretical and empirical basis for further research on improvements in the executive function of children caused by physical activity.MethodsA total of 170 children (5–6 years old) from several kindergartens were selected via multistage stratified sampling. All the children wore 7-day accelerometers (ActiGraph GT3X) to measure their daily physical activities. Parents completed the preschool children’s executive function questionnaire (BRIEF-P) to assess their daily executive function.Results(1) The total duration of physical activity (TPA) was 110.84 ± 22.52 min/day, the duration of low-intensity physical activity (LPA) was 36.23 ± 7.53 min/day, and the duration of medium- and high-intensity physical activity (MVPA) was 74.55 ± 16.77 min/day. A total of 82.6% of the children reached the recommended amount of MVPA. (2) After adjusting for body mass index (BMI), parents’ highest educational background and parents’ total monthly income, MVPA was negatively correlated with children’s total executive function score (β = −0.217, p = 0.007, 95% CI: −0.374 to −0.060, R2 = 0.034), inhibition function score (β = −0.103, p = 0.003, 95% CI: −0.170 to −0.036, R2 = 0.062), cognitive flexibility score (β = −0.079, p = 0.006, 95% CI: −0.135 to −0.023, R2 = 0.038) and working memory score (β = −0.090, p = 0.015, 95% CI: −0.163 to −0.018, R2 = 0.018). (3) There was an inverted U-shaped relationship between MVPA and children’s total executive function and working memory performance. An MVPA of 71.39 to 83.33 min/day had the greatest effect on children’s total executive function and working memory. (4) Compared with girls, boys’ MVPA time per day increased, and their total executive function, inhibitory function and working memory improved. Boys’ TPA time per day increased, and their cognitive flexibility improved.ConclusionPhysical activity can improve the executive function of children aged 5–6 years to some extent. MVPA can improve children’s executive function and subdomains, and there is a correlation between boys’ physical activity and executive function.